2014
DOI: 10.1038/jid.2014.94
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Mpzl3 Function Causes Various Skin Abnormalities and Greatly Reduced Adipose Depots

Abstract: The rough coat (rc) spontaneous mutation causes sebaceous gland hypertrophy, hair loss and extracutaneous abnormalities including growth retardation. The rc mice have a missense mutation in the predicted immunoglobulin protein Mpzl3. In this study, we generated Mpzl3 knockout mice to determine its functions in the skin. Homozygous Mpzl3 knockout mice showed unkempt and greasy hair coat and hair loss soon after birth. Histological analysis revealed severe sebaceous gland hypertrophy and increased dermal thickne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
66
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(79 citation statements)
references
References 40 publications
6
66
0
Order By: Relevance
“…The discovery that MPZL3 localizes to the mitochondria is consistent with the phenotypes that have been observed in MPZL3 mutant and knock-out mice, which display lower body weight, even in the context of high fat diets, as well as lower blood glucose levels (Cao et al, 2007; Czyzyk et al, 2013; Leiva et al, 2014). These previous observations, paired with its localization determined here, suggest MPZL3 may have other important biological roles that would be of interest to explore in future work.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The discovery that MPZL3 localizes to the mitochondria is consistent with the phenotypes that have been observed in MPZL3 mutant and knock-out mice, which display lower body weight, even in the context of high fat diets, as well as lower blood glucose levels (Cao et al, 2007; Czyzyk et al, 2013; Leiva et al, 2014). These previous observations, paired with its localization determined here, suggest MPZL3 may have other important biological roles that would be of interest to explore in future work.…”
Section: Discussionsupporting
confidence: 77%
“…MPZL3 was originally identified via its R99Q mutation in a rough coat ( rc ) mouse, characterized by a rough coat, hair loss, ulcerations in the skin, and enlarged sebaceous glands (Cao et al, 2007). MPZL3 knockout mice recapitulated this phenotype and additionally exhibited parakeratosis and increased dermal thickness (Leiva et al, 2014) as well as decreased body weight and lower levels of blood glucose compared to wild-type or heterozygous counterparts (Czyzyk et al, 2013). These phenotypes suggest an important role for MPZL3 in the skin as well as systemically.…”
Section: Resultsmentioning
confidence: 97%
“…Mpzl3 encodes an immunoglobulin protein and is expressed in the suprabasal layers of mouse epidermis, the sebaceous gland, and anagen hair follicles [3,4]. Not surprisingly, Mpzl3 knockout mice showed various skin abnormalities, including epidermal and sebaceous hyperplasia and hair loss [35].…”
Section: Introductionmentioning
confidence: 99%
“…Not surprisingly, Mpzl3 knockout mice showed various skin abnormalities, including epidermal and sebaceous hyperplasia and hair loss [35]. Interestingly, these mice also developed early onset skin inflammation with dandruff-like flakes [4]. Importantly, ZNF750 was recently shown to directly bind to MPZL3 promoter and activate its transcription in cultured human keratinocytes [6].…”
Section: Introductionmentioning
confidence: 99%
“…This observation underscores the role of epidermal differentiation in SD aetiology. Importantly, we have previously shown that knockout mice of the Mpzl3 (Myelin Protein Zero‐like 3, OMIM #611707) gene, a direct downstream target of ZNF750, develop SD‐like phenotype . These observations make the Mpzl3 knockout (−/−) mice a suitable model to study mechanisms of SD pathophysiology.…”
Section: Introductionmentioning
confidence: 99%